Biliary cystadenoma in a lion (Panthera leo) - Bizari, Thiago Gallo; Lautert, Betina Fabis; Sousa, Renato Silva de (Brazilian Journal of Veterinary Pathology, 2022)
Animals in human care often exceed the life expectancy of animals in the wild when they have veterinarian followups, no competition for space or food, and continuous care. Advanced age favors the development of mutations that often trigger cancer, which sometimes causes death. There are reports in the literature on neoplasms in lions in the liver, which are one of the main organs affected. A 20-year-old lion specimen was received for necropsy at the Federal University of Paraná, Curitiba, Brazil. Multiple cystic dilations were observed in the liver. Histologically, they were internally covered by a simple cuboidal epithelium, similar to that observed in the bile ducts, without cellular atypia. The adjacent liver parenchyma presented with mild disorganization of the hepatocyte cords. Biliary cystadenomas are benign growths formed by a thin opaque capsule filled with a slightly yellowish translucent fluid compressing the adjacent liver parenchyma, as highlighted in this case. The epithelium of the cysts was positive for anti-cytokeratin (CK) (EIA/A3E) and anti-CK7, confirming histogenesis in the bile ducts. This study reports a case of biliary cystadenoma in a Panthera leo specimen.